Eicosanoids in Invertebrate Signal Transduction Systems. - Stanley, David W. (David Warren), 1946- (Princeton : Princeton University Press, 2014)
This volume generates a new paradigm for researching and understanding the biological meaning of eicosanoids. Eicosanoid is a general term for oxygenated metabolites of certain polyunsaturated fatty acids. The compounds are extremely important in human biology, in which they are well understood. Their importance to humans, however, has tended to overshadow their broader biological significance. David Stanley seeks to change that in this book, providing a general sketch of the medical background on eicosanoids and then developing a detailed critical treatment of eicosanoid actions in inverte.
Frontmatter -- Contents -- Foreword / Howard, Ralph W. -- Acknowledgments -- Chapter 1. Introduction: A Theory of the Biological Significance of Eicosanoids -- Chapter 2. Eicosanoid Structures and Biosynthesis 11 The Mammalian Model of Eicosanoid Biosynthesis -- Chapter 3. Polyunsaturated Fatty Acids -- Chapter 4. Eicosanoids in the Reproductive Biology of Invertebrates -- Chapter 5. Eicosanoids in Invertebrate Immunity -- Chapter 6. Eicosanoids in Invertebrate Ion Transport Physiology -- Chapter 7. Emerging Eicosanoid Actions -- Chapter 8. Eicosanoids Mediate Ecological Interactions -- Chapter 9. A Research Prospectus: Approaching the Frontiers -- Abbreviations Used in References -- References -- Taxonomic Index -- Subject Index
Print version record.
Cover; Contents.
eBooks on EBSCOhost
Keywords: Eicosanoids -- Physiological effect; Cellular signal transduction; Invertebrates -- Physiology; Eicosanoïdes -- Effets physiologiques; Transduction du signal cellulaire; Invertébrés -- Physiologie; SCIENCE -- Life Sciences -- Biochemistry; Cellular signal transduction; Eicosanoids -- Physiological effect; Invertebrates -- Physiology